2001
DOI: 10.4049/jimmunol.166.10.6257
|View full text |Cite
|
Sign up to set email alerts
|

Secretory IgA Specific for a Conserved Epitope on gp41 Envelope Glycoprotein Inhibits Epithelial Transcytosis of HIV-1

Abstract: As one of the initial mucosal transmission pathways of HIV (HIV-1), epithelial cells translocate HIV-1 from apical to basolateral surface by nondegradative transcytosis. Transcytosis is initiated when HIV-1 envelope glycoproteins bind to the epithelial cell membrane. Here we show that the transmembrane gp41 subunit of the viral envelope binds to the epithelial glycosphingolipid galactosyl ceramide (Gal Cer), an alternative receptor for HIV-1, at a site involving the conserved ELDKWA epitope. Disrupting the raf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
122
1
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(131 citation statements)
references
References 69 publications
(98 reference statements)
5
122
1
1
Order By: Relevance
“…With respect to HIV, IgA (and IgM) Abs placed at either the apical or basolateral surface have been reported to block transcytosis of virus from the apical to the basolateral side in a tight epithelial cell monolayer (16,24,(33)(34)(35)(36). These findings suggest that in vivo HIV-specific IgA can both exclude HIV from mucosal epithelial cells and prevent transcytosing HIV from spreading to the lamina propria, where abundant T cells and macrophages are potential targets of infection.…”
Section: Intraepithelial Cell Neutralization Of Hiv-1 Replication By mentioning
confidence: 66%
“…With respect to HIV, IgA (and IgM) Abs placed at either the apical or basolateral surface have been reported to block transcytosis of virus from the apical to the basolateral side in a tight epithelial cell monolayer (16,24,(33)(34)(35)(36). These findings suggest that in vivo HIV-specific IgA can both exclude HIV from mucosal epithelial cells and prevent transcytosing HIV from spreading to the lamina propria, where abundant T cells and macrophages are potential targets of infection.…”
Section: Intraepithelial Cell Neutralization Of Hiv-1 Replication By mentioning
confidence: 66%
“…GalCer blot analysis was carried out as described (11). Sandwich or G M1 ELISA was done essentially as described (34) by using anti-CT Ab (Sigma) or G M1 (Sigma-Aldrich), respectively, for capture.…”
Section: Methodsmentioning
confidence: 99%
“…[12][13][14]. In addition to direct targeting of HIV-1 by neutralizing Abs (15), HIV-1 transcytosis can be blocked by disruption of rafts and by Abs against the ELDKWA epitope (7,8,10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They compared 862 HIV-1 strains and showed that 90 -97% of the isolates contain the LQAR sequence in the coiled-coil region, whereas the LELDKWAS region showed a more variable mix of 50 -97% conserved amino acids (with amino acids L-LD-W being Ͼ97% conserved). This combination of epitopes included in a vaccine may provide the conserved epitopes that have been so difficult to find in other regions of the HIV-1 envelope even though highly conserved cross-neutralization Ab-inducing epitopes have been described in the gp120 V3 region aa GPGR (47)(48)(49) and within the CD4-binding region of gp120 (50). Additional evidence suggesting the importance of inducing Abs against these gp41 epitopes is the low frequency of Ab reactivities against these regions in HIV-infected individuals (51).…”
Section: Figurementioning
confidence: 99%